Physical fitness in relation to later body composition in pre-school children - Henriksson, P.; Leppänen, M. H.; Henriksson, H.; Nyström, C. D.; Cadenas-Sanchez, C.; Ek, A.; Ruiz, J. R.; Ortega, F. B.; Löf, M. (Journal of Science and Medicine in Sport, 2019)
Objectives: Although physical fitness is considered a marker of health in youth, little is known whether physical fitness in pre-school age is related to later body composition. Thus, this study investigated (i) associations of physical fitness at 4.5 years of age with body composition 12 months later and (ii) whether improvements in physical fitness during the 12-month follow-up were associated with changes in body composition. Design: This study included 142 children, measured at 4.5 and 5.5 years, from the control group of the MINISTOP trial. Methods: Physical fitness (cardiorespiratory fitness, lower- and upper-body muscular strength and motor fitness) was measured using the PREFIT test battery. Body composition was assessed using air-displacement plethysmography. Results: In adjusted regression analyses, greater cardiorespiratory fitness, lower-body muscular strength and motor fitness at 4.5 years were associated with a lower fat mass index at 5.5 years (standardized ß= -0.182 to -0.229, p = 0.028). Conversely, greater cardiorespiratory fitness, lower- and upper-body muscular strength as well as motor fitness at 4.5 years of age were associated with a higher fat-free mass index (standardized ß = 0.255-0.447, p = 0.001). Furthermore, improvements in cardiorespiratory fitness, lower-body muscular strength and motor fitness during the 12-month follow-up period were associated with decreases in fat mass index and/or % fat mass. Conclusions: In conclusion, the results of this study provide evidence of the importance of physical fitness early in life. Nevertheless, further studies are needed in order to clarify the influence of physical fitness in the pre-school age with later health outcomes.